1997
DOI: 10.1029/96jb03281
|View full text |Cite
|
Sign up to set email alerts
|

The transition from brittle faulting to cataclastic flow in porous sandstones: Mechanical deformation

Abstract: Abstract. Triaxial compression experiments were conducted to investigate the inelastic and failure behavior of six sandstones with porosities ranging from 15% to 35%. A broad range of effective pressures was used so that the transition in failure mode from brittle faulting to cataclastic flow could be observed. In the brittle faulting regime, shear-induced dilation initiates in the prepeak stage at a stress level C' which increases with effective mean stress. Under elevated effective pressures, a sample fails … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

78
734
2
8

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 786 publications
(831 citation statements)
references
References 65 publications
78
734
2
8
Order By: Relevance
“…16-20) could not be satisfied for m \ 0.2. Homogeneous compression and weak localization (or lack of it) in compression tests with high confining stress (i.e., [200 MPa and/or m & 0.2 and therefore n & n 0 ) are in agreement with experimental results (e.g., WONG et al, 1997;WU, 2000;MENENDEZ, 1996), with recent studies of compaction bands and compacting shear bands (CHALLA and ISSEN, 2004;ISSEN 2008) and with theoretical and numerical analysis of a coupled damage-porosity model (HAMIEL et al, 2004b(HAMIEL et al, , 2005. The conditions in which strain is not localized along shear-bands could represent a transition from brittle failure to distributed cataclastic flow in which compaction, pore collapse, strain-hardening and intensive grain crushing is dominant (WU 2000;MENENDEZ 1996).…”
Section: Localized Dilation Within Shear-bands In Compression Testssupporting
confidence: 79%
“…16-20) could not be satisfied for m \ 0.2. Homogeneous compression and weak localization (or lack of it) in compression tests with high confining stress (i.e., [200 MPa and/or m & 0.2 and therefore n & n 0 ) are in agreement with experimental results (e.g., WONG et al, 1997;WU, 2000;MENENDEZ, 1996), with recent studies of compaction bands and compacting shear bands (CHALLA and ISSEN, 2004;ISSEN 2008) and with theoretical and numerical analysis of a coupled damage-porosity model (HAMIEL et al, 2004b(HAMIEL et al, , 2005. The conditions in which strain is not localized along shear-bands could represent a transition from brittle failure to distributed cataclastic flow in which compaction, pore collapse, strain-hardening and intensive grain crushing is dominant (WU 2000;MENENDEZ 1996).…”
Section: Localized Dilation Within Shear-bands In Compression Testssupporting
confidence: 79%
“…Permanent deformation (plastic yielding) occurs when the stress path intersects the yield cap or the critical state line. The elliptical shape of the cap is defined experimentally (e.g., Zhang et al 1990;Wong et al, 1997;Grueschow and Rudnicki, 2005), and this experimental work has shown that its intersection P* with the horizontal p-axis (Fig. 10a) depends on grain radius R and porosity φ through the relation P*= (φR) -1.5 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also been conducted on the micromechanics of brittle failure in porous rocks, specifically sandstone [Menendez et al, 1996;Wong et al, 1997]. These studies show that in sandstones, shear localization usually does not develop until after the peak stress has been reached.…”
Section: Introductionmentioning
confidence: 99%